Rut Dan Nomensen Sebagai Orang Asing Pembawa Berkat : Narasi Migrasi Rut Dan Pelayanan Nomensen Kepada Kaum Marjinal Merajut Inklusivisme - Daniel Sibarani (STT HKBP Pematangsiantar, 2024)
Ruth and Nommensen, as immigrants, showed how they could be a blessing to the nation in which they found themselves. Through their lives, these two characters encourage the adoption of the paradigm of inclusivism, which is important for anyone who examines their life journeys. Ruth is portrayed as a foreign and poor migrant who is treated well by the locals. Nommensen, on the other hand, was a foreigner who practiced inclusive diakonia to the marginalized indigenous population. The meeting of the migrant journey narrative in the Book of Ruth with the figure of Nommensen provides deep insight into the importance of caring for the marginalized, which comes from inclusivism. In the context of the Batak people, the figures of Ruth and Nommensen are a source of inspiration for behavior when living as foreign migrants in overseas lands, and for the church these two figures encourage the presence of a proactive attitude through transformative inclusive diaconal actions and present the name of non-violent actions.